Shifting from conveyor lines to work cellbased systems: the case of a consumer electric products manufacturer in Brazil - Miyake, Dario Ikuo; Sanctis, Renato de Lima; Banci, Felipe Salomão (Brazilian Journal of Operations & Production Management, 2010)
The division of process in short-cycle tasks performed along belt conveyors became a widely sought organizational pattern in manufacturing operations following the emergence of mass production. Later on, when manufacturers had to face the challenge to fulfi ll more diversifi ed demands, the derivation of “mixed-model assembly lines” extended the potential utilization of belt conveyors. However, more recently, a number of organizations are abandoning their utilization and switching to the adoption of work-cell based assembly systems. This article investigates such shift in operations strategy from an international perspective. Firstly, it discusses the experience of electric and electronics industries in Japan, where this trend became a major trend in the late 1990s. To support the understanding of its underpinning rationality, a conceptual review on the advantages and disadvantages of belt conveyor assembly lines is included. Next, it presents an in-depth longitudinal case study of a consumer electric products manufacturer in Brazil that embarked on a program to migrate from the utilization of conveyor lines to the work-cell based assembly system in one of itsplants. The implementation of a pilot work-cell in a kick-off project is analyzed and the prospects of the ongoing efforts to deploy similar maneuver in other facilities is presented.